Prevalence of the reversed halo sign in neutropenic patients compared with non‐neutropenic patients: Data from a single‐centre study involving 27 patients with pulmonary mucormycosis (2003‐2016). Issue 8 (21st April 2017) - Bourcier, Jessie; Heudes, Pierre‐Marie; Morio, Florent; Gastinne, Thomas; Chevallier, Patrice; Rialland‐Battisti, Fanny; Garandeau, Claire; Danner‐Boucher, Isabelle; Le Pape, Patrice; Frampas, Eric; Moreau, Philippe; Defrance, Claire; et al.
Summary: Pulmonary mucormycosis (PM) is a life‐threatening infection and the diagnosis can be challenging. The objective was to retrospectively explore the value of the RHS in our cohort of 27 patients with mucormycosis and its relation to neutropenia. This was a retrospective study including all patients with a diagnosis of probable or proven invasive PM according to the 2008 EORTC/MSG criteria between September 2003 to April 2016. Fisher's exact test and Mann‐Whitney test, with a P ‐value statistically significant under .05 ( P <.05), were used to compare neutropenic and non‐neutropenic groups. 27 patients were eligible. The RHS could be identified in 78% of cases in the neutropenic group, and was less common in the non‐neutropenic group (31%) ( P <.05). Reticulations inside ground‐glass opacity in case of RHS were present in 13 out of 15 patients (87%). Mucorales DNA detection by PCR on serum provided, a median time to the first PCR‐positive sample of 3 days (−33 to +60 days) before diagnosis was confirmed. Six patients had IPA co‐infection. In conclusion, RHS is more frequent in case of PM in neutropenic patients compare to non‐neutropenic patients. Its presence in immunocompromised patients should be sufficient to promptly start Mucorales ‐active antifungal treatment, while its absence especially in non‐neutropenic cases should not be sufficient to exclude the diagnosis.